Peran Iklan Layanan Masyarakat dalam Sosialisasi Program Busway oleh Pemprov Dki: Proses Sosialisasi Program Busway - Neonisa, Didier (Bina Nusantara University, 2011)
This research is based on the increasing numbers for traffic level in Jakarta and also less facilitated mass transportation; therefore the district government of DKI Jakarta built another mass transportation (busway) as one solution for the problems. The local government of DKI Jakarta uses mass media, especially television, to socialize the busway transportation for community. The method in this research is descriptive qualitative along with interview and related documentation as data gathering technique. The research uses theories like mass communication theory, including mass media, television, and advertising. The research result is known that public service advertising has a big role for the government of DKI Jakarta as socialization media for busway transportation; however that does not followed by the right socialization process.